STRATEGI KOMUNIKASI KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN SEKOLAH DI MTsN 3 LANGKAT - Darno Darno; Mesiono Mesiono (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
To improve the effectiveness of management in schools, supervisors, principals, employees, and teachers are expected to have strategies in communicating. Communication strategy as a method, technique or way of communication works so that we can achieve the goals that have been set. The communication strategy is always together with the following things: 1) Who am I talking to; 2) What do I mean by speaking; 3) What message to convey to someone; 4) the way I convey a message to someone; and 5) How to measure the impact of the message. This research was carried out using an approach approach, it was based on the aim of describing the informants, namely supervisors, principals, employees, teachers and students. according to the existing social situation. The quality of the description in the form of written or spoken words of the behavior of the actors that can be observed in a social situation. In this context, the researcher tries to understand the principal's communication strategy in increasing the effectiveness of school management at MTs Negeri 3 Langkat.